10x-6x+3x=-42

Simple and best practice solution for 10x-6x+3x=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-6x+3x=-42 equation:


Simplifying
10x + -6x + 3x = -42

Combine like terms: 10x + -6x = 4x
4x + 3x = -42

Combine like terms: 4x + 3x = 7x
7x = -42

Solving
7x = -42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '7'.
x = -6

Simplifying
x = -6

See similar equations:

| 0.6m+0.4n=8.4 | | Y=3g(x+2)+1 | | 8-6x+11+3x+4x-5=8+3*4 | | Y=3g(x+2)-1 | | 25y^4/10y^9 | | 40=28-5c | | Y1/4x-2 | | ln(x^2-3)=3.2 | | 0.10t+0.11(t+400)=212 | | -5x+10x-4x=15-36 | | -t=r+p*x | | 10x-20x+6x=12-16 | | 4(8x+6)=31x+1 | | 1+9x+3=2x+15+6x | | 5tan+9=0 | | 0.05a+0.09(a+5000)=1150 | | d/dx(sin(30)) | | 15x+7=14x | | 0.05a+0.09(a+5000)=7.6 | | d/dx(sin(pi/3)) | | 162=12x+0.5x^2 | | (6/(x-9))-(10/(x=3))=3 | | Grafiky=-5x-4 | | x:2(x-4)1/2(5-3x) | | TC=4+8Q+0.6Q^2 | | 2+3(x+1)=7 | | (6/(x-9))-(9/(x-7))=-15 | | r(x)=-x-7 | | 3(6-x)=27/6-6 | | (x-5)(4x-3)=(1-3x)(x+1) | | 8/1.3*100/x | | (x-6)(3x-2)=(2x-3)(x-10) |

Equations solver categories